2020
DOI: 10.3389/fcimb.2020.00383
|View full text |Cite
|
Sign up to set email alerts
|

Representative Genotyping, Recombination and Evolutionary Dynamics Analysis of TSA56 Gene Segment of Orientia tsutsugamushi

Abstract: Scrub typhus is a zoonotic disease caused by Orientia tsutsugamushi (O. tsutsugamushi). Orientia tsutsugamushi has various genotypes and more new strains with difference in sequences increasingly appeared. Whether the accurateness of one special nested PCR method which amplifies segment instead of entire open reading frame (ORF) sequence meets the current work of identifying new strains and classifying genotypes remains to be confirmed. And the origins and evolution of this organism have not been thoroughly el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…A rising trend was observed in recent years, which caused a huge disease burden in Guangzhou city. Several reasons might contribute to the increase of scrub typhus cases, such as variation of genotypes of O. tsutsugamushi ( 6 ), increased risk of exposure to vegetation with more and more parks in the city construction ( 7 ), improvement of the surveillance system, and climate change. A previous study showed that climate factors played an important role in the spread of vector-borne diseases ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…A rising trend was observed in recent years, which caused a huge disease burden in Guangzhou city. Several reasons might contribute to the increase of scrub typhus cases, such as variation of genotypes of O. tsutsugamushi ( 6 ), increased risk of exposure to vegetation with more and more parks in the city construction ( 7 ), improvement of the surveillance system, and climate change. A previous study showed that climate factors played an important role in the spread of vector-borne diseases ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…The present study suggested a high rate of genetic diversity within the isolates. The previous study suggested the presence of an elevated rate of recombination, genome duplication, and horizontal gene transfer to maintain the genetic diversity of OT isolates in Thailand (Fournier et al 2008 ), Cambodia (Duong et al 2013 ), and China (Long et al 2020 ). These recombination events are usually responsible for substantial genetic polymorphism (Yang et al 2012 ), and variable antigenicity (James et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The 56 kDa type-specific antigen gene consists of unique and cross-reacting epitopes of Orientia, contributing to the serological diversity of this species [4]. As already mentioned, sequence analysis of the 56 kDa type-specific antigen is recognized as a valuable and representative method for the genotyping of O. tsutsugamushi strains [15,16]. The 47 kDa protein is more conserved than the 56 kDa protein, but retains sufficient diversity to support genetic discrimination [6].…”
Section: Discussionmentioning
confidence: 99%